Robinow syndrome without mesomelic 'brachymelia': a report of five cases. Issue 4 (August 1986) - Bain, M D; Winter, R M; Burn, J
Abstract : A family is described in which the father and his two children had Robinow syndrome, but with no consistent brachymelia or dwarfism. Two further sporadic cases are described, one with rhizomelic brachymelia and dwarfism and the other with generalised shortening of the limbs. An attempt is also made to distinguish between the phenotype of autosomal dominant and recessive cases on the basis of the familial cases in this paper and other reported cases.